Digital help for blind people - Nesterchuk, A. M. (ТДАТУ, 2021)
From the presented above analysis we can conclude that technology is playing a vital role in tearing down barriers, and artificial intelligence is making real inroads into improving accessibility. As a result, people with disabilities have access to plenty of assistive services which help them fully participate in social life and connect to the world.
Keywords: COVID-19; Internet technologies